Clinical practice guidelines for the care and treatment of breast cancer: 13. Sentinel lymph node biopsy - Cantin, Jacques (2001)
OBJECTIVE: To provide information and recommendations to women with breast cancer and their physicians regarding what is now known about sentinel lymph node (SLN) biopsy. OPTIONS: Axillary dissection; SLN biopsy followed by backup axillary dissection; SLN biopsy. OUTCOMES: Accurate determination of cancer stage, resulting in better-informed therapeutic decisions. EVIDENCE: Systematic review of English-language literature published from January 1991 to December 2000 retrieved primarily from MEDLINE and CANCERLIT. RECOMMENDATIONS: · Axillary dissection is the standard of care for the surgical staging of operable breast cancer. · If a patient requests or is offered SLN biopsy, the benefits and risks as well as what is and is not known about the procedure should be outlined. · Patients should be informed of the number of SLN biopsies performed by the surgeon and the surgeon's success rate with the procedure, as determined by the identification of the SLN and the false-negative rate (the presence of tumour cells in the axillary nodes when the SLN biopsy result is negative). · Before surgeons replace axillary dissection by SLN biopsy as the staging procedure at their institution, they should (a) familiarize themselves with the literature on the topic and the techniques needed to perform the procedure, (b) follow a defined protocol for all 3 aspects of the procedure (nuclear medicine, surgery, pathology) and (c) perform backup axillary dissection until an acceptable success rate (as determined by the identification of the SLN and the false-negative rate) is achieved. · A surgeon who performs breast cancer surgery infrequently should not perform SLN biopsy. · A positive SLN biopsy result or failure to identify an SLN should prompt full axillary dissection. · SLN biopsy is contraindicated in women who have clinically palpable nodes, locally advanced breast cancer, multifocal tumours, previous breast surgery or previous irradiation of the breast. · Staining of tissue sections with hematoxylin and eosin, and not immunohistochemical analysis for cytokeratin, should determine adjuvant therapy. · Participation in randomized clinical trials is encouraged. [A patient version of these guidelines appears in Appendix 1.] VALIDATION: Internal validation within the Steering Committee on Clinical Practice Guidelines for the Care and Treatment of Breast Cancer; no external validation. SPONSOR: The steering committee was convened by Health Canada. COMPLETION DATE: Apr. 9, 2001.